Impact of recognition on employees` performance in the Manufacturing Industries in Tanzania: A Case of Tanga Cement Company (International Journal of Scientific Research and Management (IJSRM), 2024)
Motivation works differently among employees in an organisation. While it is generally acceptable that monetary incentive is preferable among employees but there is a debate regarding non–financial incentives such as recognition on whether they impact employee performance. This study examined the impact of recognition on employees` performance in the manufacturing industries in Tanzania by using a case of Tanga Cement Company. In conducting this study, the researchers employed a descriptive research design. Furthermore, a simple random sampling method was used to select 50 respondents which enabled the collection of quantitative data through the use of questionnaires. In analysis, the study employed descriptive and inferential statistics to analyse the data with the aid of the Statistical Package of Social Science (SPSS). The study found that media representation boosts employees’ desire to perform better, highlighting the importance of visibility and validation. Personal recognition fosters enhanced dedication, aligning with motivation theories. Receipt of recognition letters validates hard work, increasing job satisfaction and loyalty. Recognition programmes also lift employees’ morale, influencing productivity and teamwork. Public recognition fosters commitment, and positive perceptions of work, workplace, and colleagues are crucial for a positive work environment. Furthermore, verbal appreciation from supervisors and co-workers is the most impactful form of recognition, as it is immediate and personal. Receiving a recognition certificate is also significant, as formal acknowledgement can enhance employees’ work performance. The study recommends that implementing media representation strategies, establishing recognition programmes, and utilising tangible tokens of appreciation can be the best strategies to boost employee performance. This creates a positive work environment, enhances dedication, and boosts productivity by reinforcing appreciation and acknowledgement.